Hubungan Antara Sikap Dan Jarak Rumah Dengan Kepatuhan Ibu Hamil Terhadap Voluntary Counseling And Testing (VCT) - Muhamad Fauzi; Dewi Eka Stia Murni; Hani Triana; Riyanto Riyanto (Jurnal Kesehatan, 2025)
The high rate of mother-to-child HIV transmission requires special attention to help ensure a healthy future generation. VCT screening for pregnant women aims to prevent mother-to-child transmission, especially during childbirth and breastfeeding. The early detection process with Voluntary Counseling and Testing (VCT) aims to determine whether pregnant women are positive or negative for Human Immunodeficiency Virus (HIV). Compliance with VCT is crucial for early prevention and control of HIV in pregnant women. The purpose of this study was to determine the relationship between attitudes and distance from home with pregnant women's compliance with VCT. This research method used an observational study with a retrospective approach. The study was conducted in the Community Health Center “Y” working area with a population of 303 pregnant women. The sample was determined using the Slovin formula with a purposive sampling technique, resulting in 75 pregnant women. The instrument used in this study was a questionnaire, and the data analysis method used was the chi-square test. The results showed that 69.3% of mothers underwent VCT testing. There was a relationship between attitude (p 0.0001) and home distance (p 0.0001) with pregnant women's compliance with VCT. The variable that significantly influenced VCT compliance was home distance, with an Exp(B) value or OR of 11.826. Therefore, it is necessary to strengthen maternal attitudes by increasing their knowledge about VCT. The government can assist pregnant women by establishing more affordable VCT service facilities that do not endanger their pregnancy in accessing VCT services.